2016
DOI: 10.1371/journal.pone.0152394
|View full text |Cite
|
Sign up to set email alerts
|

The Domestication Syndrome in Phoenix dactylifera Seeds: Toward the Identification of Wild Date Palm Populations

Abstract: Investigating crop origins is a priority to understand the evolution of plants under domestication, develop strategies for conservation and valorization of agrobiodiversity and acquire fundamental knowledge for cultivar improvement. The date palm (Phoenix dactylifera L.) belongs to the genus Phoenix, which comprises 14 species morphologically very close, sometimes hardly distinguishable. It has been cultivated for millennia in the Middle East and in North Africa and constitutes the keystone of oasis agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
3
35
0
1
Order By: Relevance
“…Recent genetic studies suggest deep divergence in the genomes of date palms from the central and western Sahara, and north Africa (Hazzouri et al 2015), raising the possibility of a second centre of domestication, as yet unsupported archaeologically, or a process of introgressive capture (sensu Larson and Fuller 2014) from now extirpated wild palms in the Sahara, perhaps represented by remnant populations on Djerba and Kerkennah islands of Tunisia (Zehdi-Azouzi et al 2016) and by P. atlantica on Cape Verde Islands (Henderson et al 2006). The Mediterranean sister species, P. theophrasti appears to be a true wild species, now extirpated from its former distribution in the Levant, where it was recorded from sixth millennium bc finds in southern Israel (Kislev et al 2004), the identity of which is confirmed by geometric morphometrics (Rivera et al 2014;Gros-Balthazard et al 2016). Middle Holocene finds are restricted to Arabia, Pakistan, Mesopotamia and the Levant, whereas reports from the Nile Valley occur in the early second millennium bc (i.e.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent genetic studies suggest deep divergence in the genomes of date palms from the central and western Sahara, and north Africa (Hazzouri et al 2015), raising the possibility of a second centre of domestication, as yet unsupported archaeologically, or a process of introgressive capture (sensu Larson and Fuller 2014) from now extirpated wild palms in the Sahara, perhaps represented by remnant populations on Djerba and Kerkennah islands of Tunisia (Zehdi-Azouzi et al 2016) and by P. atlantica on Cape Verde Islands (Henderson et al 2006). The Mediterranean sister species, P. theophrasti appears to be a true wild species, now extirpated from its former distribution in the Levant, where it was recorded from sixth millennium bc finds in southern Israel (Kislev et al 2004), the identity of which is confirmed by geometric morphometrics (Rivera et al 2014;Gros-Balthazard et al 2016). Middle Holocene finds are restricted to Arabia, Pakistan, Mesopotamia and the Levant, whereas reports from the Nile Valley occur in the early second millennium bc (i.e.…”
Section: Resultsmentioning
confidence: 86%
“…All specimens in the UCL archaeobotanical reference collection; scale bars 1 cm that wild and domesticated populations fall towards different ends of a morphological spectrum seems clear. Indeed, studies employing geometric morphometrics (GMM) on grapes (Vitis vinifera) (Pagnoux et al 2015;Bacilieri et al 2017), as well as on other taxa such as olives (Olea europaea) (Terral et al 2004;Newton et al 2014), plums (Prunus domestica) (Ucchesu et al 2017) and dates (Phoenix dactylifera) (Rivera et al 2014;Gros-Balthazard et al 2016), which factor out size and focus instead on shape, demonstrate statistically shape differences between wild and cultivated forms of these fruits, as well as among different cultivar groups. Domesticated forms have higher L:W ratios and tend to have more pointed (acute to acuminate) ends.…”
Section: Introductionmentioning
confidence: 99%
“…AB was distinct from the other DPF for lacking a seed. The seeds of the uncultivated date palms tended to be smaller, which might occur as the result of genetic and environmental factors (Gros‐Balthazard et al, ). These physical characteristics are commonly used by farmers to evaluate the quality of the varieties.…”
Section: Resultsmentioning
confidence: 99%
“…For einkorn, emmer and barley we found a significant decrease in the SA/volume ratio with the domestication status of the grain. Changes in seed shape associated with domestication have been previously reported in other plant species, and serve as diagnostic features to distinguish true wild populations from cultivated or feral populations (Terral et al, 2010;Gros-Balthazard et al, 2016), but this has not been reported for cereals. Taking into account the relationship between the three grain dimensions, length, width and depth, a multiple regression model was generated that allowed the accurate classification of grains of a given taxa as wild or domesticated.…”
Section: Modelling Grain Domesticationmentioning
confidence: 96%